The Conservatory Documentation, the Most Important in the Universidades de Salamanca and Alcala de Henares - Roldán Tudela, Pedro (CIAN-Revista de Historia de las Universidades, 2023)
The article analyzes the conservatory documentation of the Universities of Salamanca and Alcala de Henares, which is considered the most important of these institutions because it justified its essence as an autonomous legal entity and allowed to defend its rights against usurpers. In this analysis, we first define the conservatory documentation and the two large blocks or types of which it consists, royal and pontifical, according to who sends it, the king, or the pontiff. Next, the royal privileges and the Bulls and briefs conservatories are analyzed. The conservatory documents issued for the University of Salamanca in the Middle Ages are also studied because they are the basis of the later ones confirmed in this university, which will be the ones that will incorporate the University of Alcala de Henares throughout the sixteenth century. The issuance and evolution of this type of documentation reflects the confidence of the university institution in the two powers, Spanish Monarchy and Papacy, and is an indicator of royal interventionism, which will triumph over ecclesiastical in both universities.
Keywords: Spanish Monarchy; University of Salamanca; University of Alcala de Henares; conservatory documentation